2004
DOI: 10.1080/09540120310001634001
|View full text |Cite
|
Sign up to set email alerts
|

Women from Africa living with HIV in London: a descriptive study

Abstract: There are no studies that have examined the particular needs and experiences of African women living with HIV in the UK at a time when they represent an increasingly large proportion of the UK HIV epidemic. This study explores the illness biographies and daily lives of HIV-positive African women receiving treatment in London. Sixty-two women from 11 African countries attending HIV specialist clinics in five London hospitals participated in self-completion questionnaires and in depth semi-structured interviews.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
113
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(124 citation statements)
references
References 9 publications
10
113
0
1
Order By: Relevance
“…Previous research has found that real and perceived stigma can seriously undermine access to HIV care and other support services. 32,34,35 We found that stigma had a strong impact on attendance and the findings suggest that the necessary conditions for dropping out of care were underpinned by self-stigma. Symptoms of psychological distress are highly prevalent among PLWH and have also been associated with poorer adherence to ART.…”
Section: Objective 5: Factors Influencing Outpatient Attendancementioning
confidence: 78%
See 1 more Smart Citation
“…Previous research has found that real and perceived stigma can seriously undermine access to HIV care and other support services. 32,34,35 We found that stigma had a strong impact on attendance and the findings suggest that the necessary conditions for dropping out of care were underpinned by self-stigma. Symptoms of psychological distress are highly prevalent among PLWH and have also been associated with poorer adherence to ART.…”
Section: Objective 5: Factors Influencing Outpatient Attendancementioning
confidence: 78%
“…22 Some studies have used qualitative methods and psychometric measures to try and understand why patients do not engage with care. HIV stigma is found to be a significant barrier [32][33][34][35] and health beliefs may also deter people from attending for care. 36 A qualitative study on non-attendance of HIV clinics in Scotland highlighted issues of mental health, isolation, stigma, poverty and complex social circumstances as contributing to disengagement from care.…”
Section: Chapter 1 Backgroundmentioning
confidence: 99%
“…Second, lack of information about sexual health services means that Africans often do not know where to access testing (Chinouya & Davidson, 2003;Chinouya, Musoro, & O'Keefe, 2003;Erwin & Peters, 1999;McMunn, Mwanje, & Pozniak, 1997;Traore, 2002). Third, uncertain immigration status is a powerful deterrent to seeking an HIV test and accessing care (Anderson & Doyal, 2004;Flowers et al, 2006;Maharaj, Warwick, & Whitty, 1996). Psychosocial pressures linked to immigration concerns and poverty may leave many Africans unable to cope with a positive diagnosis, as described by a qualitative study with people of sub-Saharan African origin living in France: 'You don't want to know if you have it, you want to carry on living as before.…”
Section: Hiv Diagnosis and Late Presentationmentioning
confidence: 97%
“…The question we asked about discrimination was rather broad so may not have fully captured the textured and nuanced aspects of perceived and actual discrimination (Anderson & Doyal, 2004). All participants in this study had at least two stigmatised identities; they were all HIV positive and they were also gay or black African.…”
Section: Mental Healthmentioning
confidence: 99%